The Diesel Tree Sindora glabra Genome Provides Insights Into the Evolution of Oleoresin Biosynthesis - Yu, Niu; Sun, Haixi; Yang, Jinchang; Li, Rongsheng (Frontiers in Plant Science, 2022)
Sindora glabra is an economically important tree that produces abundant oleoresin in the trunk. Here, we present a high-quality chromosome-scale assembly of S. glabra genome by combining Illumina HiSeq, Pacific Biosciences sequencing, and Hi-C technologies. The size of S. glabra genome was 1.11 Gb, with a contig N50 of 1.27 Mb and 31,944 predicted genes. This is the first sequenced genome of the subfamily Caesalpinioideae. As a sister taxon to Papilionoideae, S. glabra underwent ancient genome triplication shared by core eudicots and early-legume whole-genome duplication in the last 73.3 million years. S. glabra harbors specific genes and expanded genes largely involved in stress responses and biosynthesis of secondary metabolites. Moreover, 59 terpene backbone biosynthesis genes and 64 terpene synthase genes were identified, which together with co-expressed transcription factors could contribute to the diversity and specificity of terpene compounds and high oleoresin content in S. glabra stem. In addition, 63 disease resistance NBS-LRR genes were found to be unique in S. glabra genome and their expression levels were correlated with the accumulation of terpene profiles, suggesting potential defense function of terpenes in S. glabra. These together provide new resources for understanding genome evolution and oleoresin production.